Association of perioperative initiation of gabapentin versus pregabalin with kidney function: a target trial emulation study - He, Yanfang; Mo, Liqian; Li, Juan; Lu, Dongying; Niu, Jinlei; Li, Ying; Zeng, Qiying; Gao, Yueming (Frontiers in Medicine, 2024)
Background Gabapentinoids, such as gabapentin and pregabalin, are opioid substitutes commonly included in perioperative multimodal analgesia regimens. We investigated whether the initiation of gabapentin and pregabalin during the perioperative period have varying effects on the adverse renal outcomes. Methods This study included adult participants who received surgery in the INSPIRE database. The exposure of interest was the initiation of pregabalin or gabapentin during the perioperative period. The primary outcome was renal function decline. Secondary outcomes included incident chronic kidney disease (CKD), hospital-acquired acute kidney injury (AKI), and in-hospital mortality. We conducted a propensity score to balance the baseline characteristics. Cox proportional hazard regression was used to estimate the hazard ratio (HR) of the initiation of gabapentin compared with pregabalin. Results Among 640 pairs of pregabalin and gabapentin initiators in the matched cohort, the initiation of gabapentin was associated with a higher risk of kidney function decline (HR, 1.40; 95% confidence interval [CI], 1.04–1.89) as compared with pregabalin. After excluding participants who were diagnosed with CKD at the baseline, the initiation of gabapentin was associated with a higher risk of incident CKD (HR, 1.46; 95% CI, 1.03–2.05) as compared with pregabalin. For the in-hospital outcomes, the proportion of AKI and mortality were similar between participants initiating gabapentin and pregabalin. In addition, the risk of kidney function decline did not vary across each subgroup. Conclusion The initiation of gabapentin during the perioperative period was associated with a higher risk of kidney function decline and incident CKD as compared with pregabalin.